21. THE SITUATION OF FULL, ON-SCHEDULED IMMUNIZATION FOR CHILDREN UNDER ONE YEAR OLD IN FOUR COMMUNES OF YEN CHAU DISTRICT, SON LA PROVINCE IN 2023 (Vietnam Journal of Community Medicine, 2023)
Objectives: Describe the current status of full and timely vaccination for children under 1 year old in 4 communes of Yen Chau district, Son La province, in 2023. Subjects and methods: Using a cross-sectional study, combining qualitative and quantitative research. Quantitative and qualitative. Conducted research on 252 immunization records of children aged 12-24 months living in 04 communes Chieng On, Muong Lum, Chieng Hac, Tu Nang and 252 mothers/primary caregivers for the children. Results: The percentage of children who were fully vaccinated with 8 vaccines was 51.6%, of which full and on-time vaccination was 9%, and 33.7% were fully vaccinated and unscheduled. Fully vaccinated, on schedule with vaccines in lowland areas is higher than in highland areas and this rate is different among communes: Chieng Hac (61.9%), (50.8%), Tu Nang commune (Chieng Hac (61.9%), (50.8%). 49.2%) Chieng On (44.4%), p
Keywords: Fully vaccinated, on schedule, vaccines, children under 1 year old.